Q. 205.0( 3 Votes )

Choose the correc A. 2

B.

C. 2/x

D. 1 – x2

Answer :

Let u = cos–1 (2x2 – 1) and v = cos–1 x


Considering u = cos–1 (2x2 – 1)


Put x = cos θ θ = cos-1x ---(1)


u = cos–1 (2cos2θ – 1)


u = cos–1 (cos2θ) 2cos2θ – 1 = cos2θ


u = 2θ


u = 2 cos-1x -- From(1)


Differentiating w.r.t x we get,



Considering v = cos–1 x


Differentiating w.r.t x we get,





Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses